RURAL WOMEN PERCEPTIONS OF DIGITAL MEDIA INFLUENCE ON AWARENESS CREATION ABOUT MATERNAL HEALTH INFORMATION IN PUNJAB, PAKISTAN - TAHIRA, U; KHAN, AH; KHAN, F; RASHID, R; SAEED, S; TALHA, HU (Biological and Clinical Sciences Research Journal, 2024)
In rural settings, access to maternal health information is often limited, contributing to disparities in maternal healthcare utilization and outcomes. The main objective of the study is to find the rural women perceptions of digital media influence on awareness creation about maternal health information in Punjab, Pakistan. This cross-sectional study was conducted at the University of Lahore from August 2023 to January 2024. Data was collected from 350 participants using convenience sampling methods. Data collection involved the administration of structured surveys to participants, either in-person or through electronic means, depending on their accessibility and preferences. The survey instrument was designed to capture demographic information, including age, education level, household income, and parity, as well as assess participants’ access to digital media, frequency of usage, preferred platforms, and perceived usefulness of digital media for obtaining maternal health information. Data was collected from 350 participants. The mean age of the participants was 32.9±6.5 years Education levels varied, with 60% having primary education, 30% secondary, and 10% tertiary education. Regarding household income, 70% fell below the poverty line, while 30% were above it. Participants reported relatively high mean scores for their engagement with digital media platforms. Social media received the highest mean score of 3.8, followed by search engines with a mean score of 3.5, and maternal health websites/apps with a slightly lower mean score of 3.2. It is concluded that digital media, particularly social media platforms, play a significant role in providing access to maternal health information among rural women, despite variations in access and perceived usefulness across demographic groups.